2010
DOI: 10.1039/b923217f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced catalytic activity of Ce1−xMxO2 (M = Ti, Zr, and Hf) solid solution with controlled morphologies

Abstract: Ce(1-x)M(x)O(2) (M = Ti, Zr, and Hf) nanomaterials with controlled morphology and composition were synthesized by a two-step route for the first time. These nanomaterials exhibit high activities for hydrogen reduction and ethanol reforming reactions, and therefore, they may be useful for applications in catalysis and solid oxide fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
1
34
1
Order By: Relevance
“…This reaffirms that the exposed {100} and {110} facets exhibit greater catalytic activity as compared to {111} facets. 19 As expected the peak combustion temperature, T P , is found to broadly follow the opposite trend; more efficient catalysis is associated with a higher energy generation at lower temperature. Comparing the hydrothermal to the precipitation approaches; we find that in general for the HT series greater C(200) values and lower C(220) are observed.…”
Section: Xps and Raman Spectral Analysismentioning
confidence: 71%
See 1 more Smart Citation
“…This reaffirms that the exposed {100} and {110} facets exhibit greater catalytic activity as compared to {111} facets. 19 As expected the peak combustion temperature, T P , is found to broadly follow the opposite trend; more efficient catalysis is associated with a higher energy generation at lower temperature. Comparing the hydrothermal to the precipitation approaches; we find that in general for the HT series greater C(200) values and lower C(220) are observed.…”
Section: Xps and Raman Spectral Analysismentioning
confidence: 71%
“…The average hydrodynamic diameter was quantified using the Z-average size based upon the intensity of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 37 The refinement of the lattice constants revealed small deviation in unit cell parameters (lattice constant a = 0.541-0.545 nm) in CeO 2 of rod/tube shapes as well as ammonia precipitated crystals, indicative of small structural distortion due to crystal defects. 19 Thus the XRD patterns reveal that the asprepared ammonia precipitated and hydrothermally treated powders are crystalline CeO 2 . There is moderate broadening of the diffraction peaks in AP, which suggests smaller crystals in this sample.…”
Section: Introductionmentioning
confidence: 98%
“…However, pure CeO 2 is not suitable for the practical application because of the small specific surface area and the low thermal stability [14]. One of the efficient methods to restrain this effect and improve the property of CeO 2 support is incorporating foreign metal cations into the lattice of CeO 2 [15][16][17]. It has been reported that doping of Ti or Sn in CeO 2 can modify the catalyst surface area and insertion of doping ions improve the lattice oxygen mobility, resulting in a better redox quality [18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its extraordinary thermal and chemical stability, it is a promising material for catalytic, environmental and energy applications, such as in solid oxide fuel cells (SOFCs) [45], or for the elimination of pollutants from automobile exhaust gases, or for fluid catalytic cracking or dehydrogenation of ethylbenzene to styrene. With respect to catalysis, CeO 2 is a valuable support material for the low-temperature water–gas shift reaction and preferential oxidation of CO in hydrogen-enriched atmospheres.…”
Section: Introductionmentioning
confidence: 99%